QUALITY CHARACTERISTICS OF GOAT MILK ICE CREAM WITH FORTIFICATION BROWN SEAWEED (Sargassum sp.) - Yance Gusriayanti; Dahlia Dahlia; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aimed to determine the quality characteristics of goat's milk ice cream with fortified brown seaweed (Sargassum sp.). The research method used was a non-factorial completely randomized design (CRD) with 4 levels of treatment, namely R0 (0% Sargassum sp.), R1 (5% Sargassum sp.), R2 (10% Sargassum sp.), R3 (15% Sargassum sp.). The test parameters carried out were organoleptic quality analysis of appearance, aroma, taste, and texture. The results showed that goat's milk ice cream with fortified brown seaweed (Sargassum sp.) had a significant effect on organoleptic quality characteristics at the 95% confidence level. The value of organoleptic quality of appearance, aroma, taste and texture of the best treatment was R3 (15% Sargassum sp.), with organoleptic value of appearance 3.80, aroma 4.00, taste 3.40, and texture value 4.40. The average organoleptic value was 4.00 with the characteristic appearance of the ice cream being slightly dark brown; specific aroma of ice cream, typical of seaweed; ice cream flavor, slightly sweet; and the texture of the ice cream, soft.Keywords: Characteristics, Goat's milk, Ice cream, Sargassum sp.